Kompetensi Guru MI Ma’arif Setono Ponorogo dalam Pembelajaran Sains Berbabasis Pendidikan Karakter - Athok Fu'adi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2012)
Abstract : In learning science, a teacher of Islamic elementary scholl must master the science materials and techniwues of learning science and assessment as well so that students can achieve the specified indicators. A teacher’s success will be depended on: the first it depended on his personality, secondly it depended on the mastery of the methods, third it depended on the frequency and intensity of interactive activities between teacher with students, and fourth, whatever the reason, the most important is the appearance of the material, mastering the learning strategies and develop the character education in responbility, respect and attention, caring, and honest. Key Words: Teachers, Competency, Learning, and Character.